Investigation into the Presence or Absence of Solid Particles Generated from Thermal Processes in the Aerosol from an Electrically Heated Tobacco Product with and without Filter Elements - Teemu Kärkelä; Jean-Christophe Ebinger; Unto Tapper; Olivier Robyr; Tauno Jalanti (Aerosol and Air Quality Research)
Abstract Heated Tobacco Products (HTPs) were developed as healthier alternatives to cigarettes, which release thousands of chemicals owing to the combustion of tobacco. One HTP is the Electrically Heated Tobacco System (EHTS) from Philip Morris International, which heats instead of burns the tobacco material and produces significantly fewer emissions than traditional cigarettes, as extensively substantiated by independent research groups. Published studies have also confirmed the absence of solid particles in these emissions, which may be due to the filter elements between the tobacco portion and the mouthpiece in the EHTP; however, to the best of our knowledge, the role of these filters has never been investigated. Thus, to determine whether solid particles formed in any part of the product during use, we collected the aerosol from an EHTP with and without filter elements under heated and unheated testing conditions. Both of the analytical methods we applied showed that no solid particles originating from thermal processes were present in the aerosol.